Management of public safety with the use of visual monitoring in the city and county of Walbrzych = Zarządzanie bezpieczeństwem publicznym z wykorzystaniem monitoringu wizyjnego na przykładzie miasta i powiatu wałbrzyskiego - Tabaczniuk, Tadeusz (Zielona Góra: Faculty of Economics and Management Press)
The paper presents basic legal conditions related to the operation and types of video monitoring systems. These considerations include the attempt to diagnose the impact of the use of video monitoring systems on the number of new cases initiated on the basis of the crime rate in the area of the city and county of Walbrzych. The article contains a comparative study based on this indicator in the studied area, in Poland and the EU countries.
Keywords: bezpieczeństwo publiczne; społeczność lokalna; monitoring wizyjny; dane statystyczne; public safety; local society; visual monitoring; statistical data